An Updated Look at Television-Related Pediatric Head and Neck Injuries: Safer Products and a Shifting Paradigm. Issue 4 (18th June 2021) - Oleck, Nicholas C.; Berlin, Ryan S.; Leverant, Elizabeth; Paskhover, Boris
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Television tip-over injuries have been designated a top-five hidden home hazard by the United States Consumer Product Safety Commission. In this study the authors utilize the National Electronic Injury Surveillance System (NEISS) Database to provide an updated look at television-related head and neck injuries in the United States pediatric population. The NEISS Database was accessed for all television-related head and neck injury reports from January 2000 to December 2018 in patients under 18 years of age. Demographic data including age, sex, and race were also obtained. Narrative descriptions of each injury were also individually reviewed and categorized by specific type of injury. Miscoded reports were excluded. Between January 2000 and December 2018, 5944 NEISS reports of television-related injuries met inclusion criteria, corresponding to an estimated total of 159, 785 injuries nationally during this period. The average patient age at time of evaluation was 4.11 years with a male predominance of 61.3%. Total number of injuries — and weighted national estimates — remained relatively stable between 2000 and 2006, peaking in 2009 (450 reported cases, 12, 004 estimated national total). Between 2009 and 2018 the number of reported injuries, and corresponding national estimates, saw a 75.8% and a 72.1% decrease, respectively. Television-related head and neck injuries have declined dramatically in the United States since 2009. The underlying cause of this decline is likely multifactorial, and additional steps to improve the safety of these products are necessary to continue to ensure the safety of all children in the United States.